Sinking Organic Particles in the Ocean—Flux Estimates From in situ Optical Devices - Giering, Sarah Lou Carolin; Cavan, Emma Louise; Basedow, Sünnje Linnéa; Briggs, Nathan; Burd, Adrian B.; Darroch, Louise J.; Guidi, Lionel; Irisson, Jean-Olivier; Iversen, Morten H.; Kiko, Rainer; Lindsay, Dhugal; Marcolin, Catarina R.; et al. (Frontiers in Marine Science, 2020)
Optical particle measurements are emerging as an important technique for understanding the ocean carbon cycle, including contributions to estimates of their downward flux, which sequesters carbon dioxide (CO2) in the deep sea. Optical instruments can be used from ships or installed on autonomous platforms, delivering much greater spatial and temporal coverage of particles in the mesopelagic zone of the ocean than traditional techniques, such as sediment traps. Technologies to image particles have advanced greatly over the last two decades, but the quantitative translation of these immense datasets into biogeochemical properties remains a challenge. In particular, advances are needed to enable the optimal translation of imaged objects into carbon content and sinking velocities. In addition, different devices often measure different optical properties, leading to difficulties in comparing results. Here we provide a practical overview of the challenges and potential of using these instruments, as a step toward improvement and expansion of their applications.